Cardiovascular Imaging in Pregnancy: Valvulopathy, Hypertrophic Cardiomyopathy, and Aortopathy - Ismail, Haneen; Bradley, Andrew J.; Lewis, Jannet F. (Frontiers in Cardiovascular Medicine, 2022)
Pregnancy is associated with profound hemodynamic changes that significantly impact the cardiovascular system. These changes are particularly impactful in women with underlying heart disease. Management of pregnant women with cardiovascular abnormalities requires consideration of the well-being of both the woman and the developing fetus. Clinical evaluation, starting before and then continuing throughout pregnancy, is the foundation of this management with imaging playing a key role in patient risk stratification and monitoring. This review discusses the role of imaging for pregnant women with valvular diseases, hypertrophic cardiomyopathy, and aortic pathology. We will begin with a brief overview of general patient assessment and discussion of the value added by different imaging modalities.